AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN FRAKSI DAUN Colocacia esculenta L. DENGAN METODE KLT-BIOAUTOGRAFI DAN DIFENILPIKRIL HIDRAZIL - Herwin Herwin; Muzakkir Baits; Ririn Ririn (As-Syifaa Jurnal Farmasi, 2015)
The aim of the research to determine the antibacterial and antioxidant activity of Colocacia esculenta fraction leaves derive from Pare-Pare South Sulawesi in using TLC- Bioautography and diphenilpycril Hydroxil. Screening antibacterial activity test of the Colocacia esculenta fraction leaves exhibited in concentration 1% active on pathogenic bacteria Salmonella thypi. Based on either antibacterial and antioxidant activities by TLC-Bioautography showed that fraction at Rf 0.70 value active on bacteria Salmonella thypi and antioxidant active as well. Identification of active chemical compound showed flavonoid compound using Iodium-KI and antimo (III) clorida as reagent.